IMPLEMENTATION of HIV/AIDS MITIGATION POLICIES at AIDS MANAGEMENT COMISSION (KPA) OF MAKASSAR CITY - Natasyah Alya Syelsyabila; Andi Aslinda; Andi Cudai Nur; Ismail Ismail (Universitas Negeri Makassar, 2026)
This research is a type of qualitative research that is descriptive and aims to determine the implementation of the Makassar City HIV/AIDS Management Policy (KPA). The data sources used are primary data sources and secondary data sources. In determining informants using purposive sampling technique. Data collection techniques were carried out using interviews, observation and documentation. The informants in this research were the AIDS/HIV Program Manager, Makassar City Health Service, Head of Social Rehabilitation Division, Makassar City Social Service, Mitra Husada Foundation Prajangkau Officer, Guardians/Patients infected with HIV/AIDS. The results of this study indicate that the Implementation of the HIV/AIDS Control Policy (KPA) in Makassar City has not been optimally implemented. There are 4 sub-indicators that are considered based on the theory of George C. Edward III (1980). This can be seen in two indicators that have been implemented well, namely the disposition and bureaucracy indicators and two indicators that have not been optimal in their implementation, namely the communication and resource indicators. This is because the communication process through socialization has not fully reached the key population and there is still stigma/discrimination against PLWHA and there are still inhibiting factors in the resource variable which should be the most optimized variable. The inhibiting time in the implementation of HIV/AIDS control (KPA) in Makassar City is related to social stigma and discrimination against PLWHA (People with HIV/AIDS), limited special budgeting for HIV/AIDS programs, and limited Human Resources (HR).